2013
DOI: 10.1021/bm400406x
|View full text |Cite
|
Sign up to set email alerts
|

Carboxymethyl-Chitosan-Tethered Lipid Vesicles: Hybrid Nanoblanket for Oral Delivery of Paclitaxel

Abstract: We describe the development and evaluation of a hybrid lipopolymeric system comprising carboxymethyl chitosan (CMC), covalently tethered to phosphatidylethanolamine units on the surface of lipid nanovesicles, for oral delivery of paclitaxel. The bioploymer is intended to act as a blanket, thereby shielding the drug from harsh gastrointestinal conditions, whereas the lipid nanovesicle ensures high encapsulation efficiency of paclitaxel and its passive targeting to tumor. CMC-tethered nanovesicles (LN-C-PTX) in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(36 citation statements)
references
References 50 publications
1
35
0
Order By: Relevance
“…Doses ranging from 0.5 to 10 mg/kg were used for intravenous route [18][19][20][21][22] and ranging from 2 to 100 mg/kg for oral route [18,[23][24][25] but oral doses were not below 10 mg/kg in most studies [26][27][28][29][30][31]. The calculated (mg/kg) dose by extrapolation for rat is around sixfold higher than for adult human because the surface area to weight ratio depends on species [32].…”
Section: Discussionmentioning
confidence: 99%
“…Doses ranging from 0.5 to 10 mg/kg were used for intravenous route [18][19][20][21][22] and ranging from 2 to 100 mg/kg for oral route [18,[23][24][25] but oral doses were not below 10 mg/kg in most studies [26][27][28][29][30][31]. The calculated (mg/kg) dose by extrapolation for rat is around sixfold higher than for adult human because the surface area to weight ratio depends on species [32].…”
Section: Discussionmentioning
confidence: 99%
“…4 Many researchers have attempted to coat the nanoparticles with chitosan or its derivatives to increase mucoadhesion. [10][11][12] Positively-charged chitosan can adhere to negatively charged sialic and sulfonic acids in the mucus layer via electrostatic interaction. 13 Yet another approach involves thiolated polymers have been developed to improve the mucoadhesive properties of nanoparticles, and these are often termed "thiomers".…”
Section: Introductionmentioning
confidence: 99%
“…41 PTX was not detected in plasma and other organs of the animal, showing that the formulation effectively localizes the drug at the tumor site only ( Figure 5). Previous studies with intravenous injection of Taxol in a subcutaneous murine melanoma model have shown significant PTX distribution in the plasma and other organs (such as liver and lung) at 2 h, 17,42 while that from LG-PTX showed drug levels only in the tumor. Other references have shown that only a fraction of the intravenous Taxol dose (5%, ~10 µg/g) is accumulated in subcutaneous tumors, 43,44 while a substantial fraction of drug is accumulated in the tumor when LG-PTX is used (33%, ~343 µg/g).…”
Section: In Vivo Ptx Biodistributionmentioning
confidence: 87%
“…In such a scenario, the strategy of utilizing nanotechnology in the field of oncology presents huge opportunities to overcome these limitations and improve the therapeutic ratio for effective regional delivery of radiosensitizers. 16 A number of nano-sized carriers [17][18][19] and synthetic poly(ethylene glycol) (PEG)-based gels have been studied as drug carriers [20][21][22][23][24] but have inherent limitations.…”
mentioning
confidence: 99%